2006
DOI: 10.1088/0957-4484/17/4/040
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and photoluminescence of high-quality ternary CdSSe nanowires and nanoribbons

Abstract: Ternary alloy CdSSe nanowires and nanoribbons were successfully grown through a one-step thermal evaporation route using Au as a catalyst. The nanostructures obtained are uniform in diameter, and have smooth surfaces. High-resolution transmission electron microscopy, energy dispersive x-ray spectra and x-ray diffraction showed that both the nanowires and the nanoribbons have high-quality single-crystalline nature, and their compositions can be determined as CdS(0.6)Se(0.4) and CdS(0.3)Se(0.7), respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 22 publications
(25 reference statements)
2
53
0
1
Order By: Relevance
“…As a result, various ternary alloys have recently attracted a great deal of attention for their ability to achieve a wide range of band-gaps, [1][2][3][4][5][6][7][8][9][10][11][12] Additionally, nano-materials, such as nano-wires and nano-ribbons, offer greater versatility by providing a wider range of alloy composition and band-gap modulation which is unachievable using traditional epitaxial film materials due to lattice strain at the substrate interface. 13 Ternary chalcogenide semiconductors, particularly cadmium sulpho-selenide (CdS x Se 1Àx ) alloys, have been intensely studied 8,[14][15][16][17][18][19] in part due to the remarkably broad range of stable stoichiometries that can be attained, owing to the small lattice mismatch among the constituent anions. 14 CdS has a wurtzite (hexagonal) crystal structure with lattice parameters of a ¼ 4.16 Å and c ¼ 6.76 Å , while CdSe, also a wurtzite, has lattice parameters of a ¼ 4.30 Å and c ¼ 7.02 Å .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, various ternary alloys have recently attracted a great deal of attention for their ability to achieve a wide range of band-gaps, [1][2][3][4][5][6][7][8][9][10][11][12] Additionally, nano-materials, such as nano-wires and nano-ribbons, offer greater versatility by providing a wider range of alloy composition and band-gap modulation which is unachievable using traditional epitaxial film materials due to lattice strain at the substrate interface. 13 Ternary chalcogenide semiconductors, particularly cadmium sulpho-selenide (CdS x Se 1Àx ) alloys, have been intensely studied 8,[14][15][16][17][18][19] in part due to the remarkably broad range of stable stoichiometries that can be attained, owing to the small lattice mismatch among the constituent anions. 14 CdS has a wurtzite (hexagonal) crystal structure with lattice parameters of a ¼ 4.16 Å and c ¼ 6.76 Å , while CdSe, also a wurtzite, has lattice parameters of a ¼ 4.30 Å and c ¼ 7.02 Å .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of CdS x Se 1Àx alloy nano-material morphologies have been synthesized, including nano-wires, nano-ribbons, nano-belts, nano-sheets, nano-crystals, and nano-particles with a variety of aspect ratios and stoichiometries. 3,14,16,18,19 The diversity of electronic and spectral properties of CdS x Se 1Àx alloy nanostructures has great potential applications in tunable optoelectronic devices, such as color engineered displays and lighting, 19 multi-spectral detectors, 13 full-spectrum solar cells, 23 and broadly tunable nanolasers. 8,15,24 Therefore, a detailed examination of the electronic structure and corresponding optical emission is essential to determine the full potential of these functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…The Se-doped and undoped CdS nanoribbons were synthesized by physical evaporation of commercial-grade CdS and CdSe nanopowder in the presence of a Au catalyst [18,19] . We investigated the optical waveguide properties of the nanoribbons using a commercial near-field scanning optical microscope (SNOM) and spectroscopy system [20,21] , which consists of a scanner NSOM-100 from Nanonics Co., Israel, a control system SPM-100 from RHK Co., U.S and a spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Such hybrid materials are finding applications in nanoelectronics and nano photonics, where it is rather beneficial to have semiconducting nanostructures with continuously tunable band gaps. Recent advances in 0D and 1D ternary semiconductor structures have shown that their band gaps and light emissions could also be tuned gradually by changing their constituent stoichiometries, and based on these composition modulated nanostructures, multi-wavelength lasers, wavelength converters, optical diodes, and nano photodetectors have been realized experimentally [42][43][44][45][46][47][48][49][50][51][52]. For their applications in integrated devices and systems, direct growth of these band gap engineered 2D monolayer materials are proving to be very useful as discussed in a recent review covering the recent progress on the BGE of atomically thin 2D semiconductor alloys.…”
Section: Other Hybrid 2d-monolayersmentioning
confidence: 99%